Charlotte Scott letter to Thomas Kent regarding Ruddy Shelduck sightings, December 1, 1981 - Scott, Charlotteet al (1981)
Rare bird sighting for two Ruddy Shelducks at Promise City in October 1981. The sighting is reported in a letter from Charlotte Scott to Tom Kent on December 1, 1981. Charlotte also reports a sighting of a Snowy Owl at Benny Davis Lake. Epson - sheet feed